A BJT-based CMOS Temperature Sensor With a ±0.94°C 3σ-inaccuracy From −40°C to +150°C - Park, Tae-June; Boo, Jun-Ho; Lim, Jae-Geun; Kim, Hyoung-Jung; Lee, Jae-Hyuk; Park, Seong-Bo; Cho, Won-Jun; Ahn, Gil-Cho (Journal of semiconductor technology and science, 2025)
This paper presents a BJT-based CMOS temperature sensor designed for an extended temperature range. In the sensing frontend, a β-compensation technique is employed to mitigate the effects of the finite current gain (β) of PNP transistors. Additionally, bitstream-controlled dynamic element matching (DEM) is applied to address mismatch errors in current sources and PNP transistors. The readout circuit based on 1-bit second-order incremental ∆Σ ADC is configured with a minimum number of sampling switches to mitigate the impact of increasing switch leakage currents at high temperatures. Furthermore, system-level low-frequency chopping (CHL) is implemented digitally, removing the need for extra switches. Fabricated in a 0.18-µm CMOS process, the proposed sensor occupies an area of 0.63 mm2 . The sensor is accurate to within ±0.94◦C (3σ) after one-point trimming from −40◦C to +150◦C. It achieves a resolution figure of merit (FoM) of 21.17 pJ·K 2 at 27◦C, with a conversion time of 20 ms and a power consumption of 22.23 µW from a 1.8 V supply. KCI Citation Count: 0